The Noncompliant Patient - James B. Young; Justin C. Cordova (Methodist DeBakey Cardiovascular Journal)
This issue’s Poet’s Pen is an experiential work submitted by Captain Justin C. Cordova, MD, from the Department of Anesthesiology at Walter Reed National Military Medical Center in Bethesda, Maryland. The submission was a response to an invitation for our readers to submit poems for consideration of publication. Captain Cordova’s work, “Against Medical Advice,” is an engaging and provocative poem that focuses on a disturbing healthcare provider challenge—attempting to deliver “best care” to patients who, for countless reasons, choose a pathway we label as noncompliance or against medical advice.